2022
DOI: 10.1002/pcn5.13
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacological treatment of schizophrenia: How far have we come?

Abstract: Schizophrenia is a chronic and often severe mental disorder for which antipsychotic drugs are the cornerstone of treatment. Although the essential mechanism of action of these drugs has not changed much since they were first discovered in the 1950s, there have been numerous advances in the context in which these drugs are prescribed, as well as in the considerations for their optimal use. In this review, we summarize five selected issues in which the psychopharmacological treatment of schizophrenia has most ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 113 publications
(226 reference statements)
0
3
0
Order By: Relevance
“…The research about pharmacological treatment showed progress, as seen in the overlay visualizations that now research has shifted toward the new generation of atypical antipsychotics. The research about treatment are still evolving to develop interventions that resulting in efficacy of the treatment (Ganguly et al, 2018) (Rubio & Kane, 2022). The forth clusters described the genetic and mechanism of schizophrenia as shown by keyword -brain‖, and -polymorphism‖ as schizophrenia is strongly correlated with genetic predisposition (Laksono et al, 2019) (Maritska et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The research about pharmacological treatment showed progress, as seen in the overlay visualizations that now research has shifted toward the new generation of atypical antipsychotics. The research about treatment are still evolving to develop interventions that resulting in efficacy of the treatment (Ganguly et al, 2018) (Rubio & Kane, 2022). The forth clusters described the genetic and mechanism of schizophrenia as shown by keyword -brain‖, and -polymorphism‖ as schizophrenia is strongly correlated with genetic predisposition (Laksono et al, 2019) (Maritska et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Since the introduction of chlorpromazine and haloperidol seven decades ago, the number of drugs for psychosis has steadily increased with new drug entities and formulations resulting in dozens of treatment options for schizophrenia and other major psychiatric disorders (Rubio and Kane, 2022;Taylor et al, 2021). Competent use of drugs for psychosis requires clinical experience and knowledge of sound dosing practices.…”
Section: Introductionmentioning
confidence: 99%
“…The available pharmacotherapy of schizophrenia primarily focuses on the control of psychosis and has a limited efficacy on the negative symptoms. On the other hand, cognitive disorders in the course of schizophrenia are not subject to treatment with classic antipsychotic drugs, and additionally, sometimes such pharmacotherapy may exacerbate these disorders [2]. This is a very important medical problem because the large changes in cognitive functions are very often noticeable in people suffering from schizophrenia.…”
Section: Introductionmentioning
confidence: 99%